2014
DOI: 10.1093/occmed/kqu099
|View full text |Cite
|
Sign up to set email alerts
|

A survey of sitting time among UK employees

Abstract: There is a pressing need for future workplace health interventions to reduce employee sitting times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 25 publications
8
58
0
Order By: Relevance
“…In addition, observational studies have shown that time spent sitting, independent of levels of moderate-to-vigorous physical activity, are positively correlated with the risk of diabetes, cardiovascular disease, some cancers and premature mortality [39–41]. Because those who spend more time sitting at work may also spend more time sitting during leisure time [9], strategies to prevent sedentary behaviors at work like the one tested in this study may have important health implications in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, observational studies have shown that time spent sitting, independent of levels of moderate-to-vigorous physical activity, are positively correlated with the risk of diabetes, cardiovascular disease, some cancers and premature mortality [39–41]. Because those who spend more time sitting at work may also spend more time sitting during leisure time [9], strategies to prevent sedentary behaviors at work like the one tested in this study may have important health implications in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expansion of service occupations has reduced physical activity by 20 % at the workplace since 1960, which could be 35 % by 2030 [8]. For those working in offices, 65–75 % of their work time is spent sitting, with time spent sitting at work accounting for more than half of the total daily sitting time on work days [911]. Only recently has exercise been proposed as a worksite strategy to improve performance, concentration and satisfaction at work [12].…”
Section: Introductionmentioning
confidence: 99%
“…These associations may, however, be attenuated in people who undertake regular moderate-to-vigorous physical activity 40. Furthermore, those who spend more time sitting at work also spend more time sitting during leisure time 20. A number of studies in relation to television viewing have shown adverse associations with mental health, well-being41–43 and muscle strength 44 45.…”
Section: Sedentary Behaviour Within the Context Of Human Physical Actmentioning
confidence: 99%
“…The key evidence that underpins these recommendations comes from two key sets of studies. Data collected as part of a longer term retrospective national health and fitness survey,52 63 where independent of physical activity and controlled for other confounding factors, there was a threshold for significant risk reduction in individuals who performed work that involved (at least) standing on one's feet (or some movement) for more than 2 h/day; and where the greatest risk reduction was demonstrated in those standing for at least half their day to a full day (4+ hours).Data presented from a number of observational or acute interventional studies where there were pronounced changes in cardiometabolic and ergonomic risk factors (eg, energy expenditure, blood glucose, insulin, muscle function and joint sensations), when the total accumulated time exceeded 2 h/day 5 7 10–13 20 27 33 45 54 58 64…”
Section: Evidence Evaluation and The Recommended Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation